Suicide and its risk factors - An ecological study - Tamilarasan Muniyapillai; Karthikeyan Kulothungan; K Nawin Jai Vignesh; Sathya CM Keerthi; Sherin Rosetta Godwyn; SB Shivashankari; Shivanjali Raje B Bhonsle; Shanmuga Priya Krishnakumar; Shivani Devi Suresh (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: There is tremendous variation in both the prevalence of suicide and the factors that contribute to its occurrence across geographic locations, cultures, and time. Therefore, the present study aims to identify the various socio-demographic risk factors and psychosocial stressors using population data. MATERIALS AND METHODS: The countries that were included in the study were based on data from the World Health Organization. We considered the top ten suicide countries and the ten lowest suicide nations. We searched five global databases for the most recent socio-demographic data and data on psychosocial stressors during the period of August and September 2022. We analyzed the correlation between suicide rates and various factors, and we considered a P value of less than 0.05 to be statistically significant. RESULTS: The correlation of suicide with sociodemographic factors like age (P 0.246), gender (male, P 0.357, and female, P 0.357), net enrolment rate (P 0.725), gender parity index (P 0.929), urban population percentage (P 0.571), marital status (male, P 0.345, and female, P 0.752), and literacy rate percentage (P 0.199) was not significant. The correlation of suicide with psychosocial stressors like unemployment percentage (P 0.552), alcoholism percentage (P 0.271), the prevalence of depression (P 0.523), the number of psychiatrists (P 0.605), the number of mental hospitals (r = -0.090, P 0.713), and the poverty rate percentage (P 0.538) were also not significant. CONCLUSION: Suicide is a major public health issue, yet global suicide data is scarce. Sociodemographic factors like age, urbanization, and literacy rate were negatively correlated, whereas psychosocial stressors like unemployment, alcohol misuse, and poverty were positively correlated, but none were significantly associated.